Uma metodologia para simulação computacional de catéteres de aspiração endotraqueal - implementação de modelo visoelástico de Oldroyd-b - Igor Martini Florencio (2019)
Patients with artificial airways have to undergo an endotracheal suction procedure periodically to remove retained pulmonary secretions. This procedure may result in developing adverse reactions, which needs to be minimized. The procedure´s improvement, and the catheter´s geometry, are closely bound to the secretion´s viscoelastic rheology. Aiming to provide a methodology for future studies of catheter´s geometry improvements, the present work aims to introduce a methodology able to simulate computationally the viscoelastic effects of pulmonary secretions through Oldroyd-B model implemented via a User Defined Function (UDF) in ANSYS FLUENT. This work compares CFD simulations and Experimental test results from a mucus simulator solution, composed by Polyethylene Glycol 5.000.00g/mol in 2%wt aqueous solution. Results show that the model achieved quantitatively accurate predictions of pressure differentials measured experimentally.